Between Identity and Anonymity: Art and History in Aharon Megged's Foiglman - Brenner, Rachel Feldhay (AJS review, 1995)
In a recent article, “Israeli Literature Over Time,”Aharon Megged describes his work as “unremittingly concerned with burning national issues,” mainly with the issue of Israel′s relationship to the Diaspora.1 Megged′s intense preoccupation with the Zionist ideology of the negation of the Diaspora emerged in his 1955 story “Yad va-shem” (“The Name”). The story presents a scathing criticism of Israel′s dissociation from the history of the Diaspora and especially from the catastrophe of the Holocaust. “Yad va-shem” was followed by an article entitled “Tarbutenu ha-yeshana ve-ha-hadasha” (“Our Old and New Culture”) in which Megged deplored Israel′s severance of its Diaspora roots and urged a reexamination of the negative attitude toward the destroyed European Jewish culture.In 1984, Megged published Massa ha-yeladim el ha-aretz ha-muvtachat (“The Children's Journey”), a novel based on a true story about a group of young survivors of the Holocaust on their way to Palestine.3 This work, as Dan Laor notes in his review, “offers a perspective of the Diaspora in the Holocaust which differs from [the typical Israeli attitude of] contempt infused with pity” toward the Diaspora Jew.